Simultaneous Cationization and Antimicrobial Treatment of Cotton Khadi Fabric with Poly-Hydroxy Methyl Amino Sillicone (PHAMS) and Poly Ethylene Glycol (PEG). (2017) - Kar, Tapas Ranjan; Kaware, Runali; Sajid, Mohammed; Samanta, Ashis Kumar
Abstract: Cotton Khadi fabric is treated with eco-friendly anti- microbial agents like Polyethylene Glycol (PEG -200), Poly-Hydroxyl Amino Methyl Silicone (PHAMS) and Citric Acid (CA) individually and in their blends as compared to treatment with epoxy-propyl-trimethyl-ammonium chloride (EPTAC) in presence of MgCl2 as mild acidic catalyst by low tensioned padding and drying at 100 ° C for 10 min. followed by curing at 120 ° C for 4 min. to investigate the effect of such treatment on important textile related properties and microbial resistance and dye-ability with reactive dye. For presence of –OH group, PEG, PHAMS and EPTAC have ability to react with –OH groups of cellulose under acidic catalyst to bound to cellulose macromolecules forming ether linkage and can produce a modified cationized cotton attaching –NR3 + groups of EPTAC and –NHR2 + or –NH3 + groups of PHAMS. Highest Antimicrobial and salt free dyeing with reactive dye was achieved by combined treatment of PEG and PHAMS (in 3:1 ratio) in presence of 1/5 th of magnesium chloride. FTIR, XPS and TGA studies have been carried out to understand the nature of reaction and modification occur to support reaction mechanism discussed. The effectiveness of the antimicrobial properties have been assessed by measuring the loss of tensile strength by soil burial test and also by testing as per AATCC-100 and AATCC-147.